2016
DOI: 10.3329/sja.v13i2.26575
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nitrogen nutrition on productivity and nutrient use efficiency of potato (Solanum tuberosum L.) In an inceptisol of west Bengal, India

Abstract: The experiment was carried out at the District Seed Farm, Adisaptagram, Hooghly (West Bengal), India during two consecutive winter seasons of 2011-12 and 2012-13 to find out optimum N dose of potato cultivars for getting higher yield as well as to identity efficient potato cultivars regarding N use. Average yield of potato cultivars increased significantly with increase in N supply up to 225 kg N ha . Nitrogen use efficiency (NUE) decreased towards higher N levels for all cultivars. NUE of Kufri Himalini was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
4
7
0
Order By: Relevance
“…The lower PE might indicate that the crop did not utilize the absorbed N for the production of maximum pod yield. Related findings on PE of N on potato were reported by Banerjee et al (2015). The authors indicated that at high uptake of N the PE decreases a luxury consumption of N that might not contribute to physiological processes.…”
Section: Physiological Efficiencysupporting
confidence: 63%
“…The lower PE might indicate that the crop did not utilize the absorbed N for the production of maximum pod yield. Related findings on PE of N on potato were reported by Banerjee et al (2015). The authors indicated that at high uptake of N the PE decreases a luxury consumption of N that might not contribute to physiological processes.…”
Section: Physiological Efficiencysupporting
confidence: 63%
“…This is in line with the study of (Badr et al, 2012). On the contrary, Banerjee et al (2015) found out that NUE decreased with an increase in N rate. For the interaction, the highest value of NUE was recorded at FI×N3 (236.44 kg/N kg) whereas the latest was obtained from RF×N1(56.30 kg/N kg) (figure 2k and l).…”
Section: Nitrogen Use Efficiencysupporting
confidence: 91%
“…These authors showed that at high P uptake the PE of crops decreases and the PE of P would depend on varieties. Nutrient efficiency of plants depends on: soil factor of production potential, chemical species of the fertilizer used and plant factors of interaction with environmental factor and root microbe [20,22,24].…”
Section: Physiological Efficiency (Pe) Of Pmentioning
confidence: 99%